Soil Nutrient Dynamics in Different Forest-Ecosystem in Almora-Binsar Area of Central Himalaya - Joshi, B.K. (Journal of Soil and Water Conservation, 2022)
Open grazing, burning and other human encroachment increasingly threaten for the forest ecosystem of the temperate hill region of Indian Himalaya. At present these are practiced as multiple uses, including maintaining the environmental balance of the region. The present study was conducted to assess the effect of the human encroachments in different forest ecosystems and discuss the prospect for improving their requirement by initiation of community forestry, in the context of regular deterioration in forest ecosystems. Total six types of forest were considered for the present investigation, are both natural and planted one, including herb, shrubs and tree canopy It is observed that the woody patches with grass are affected by frequent grazing, leaf litter collection and forest fire interferences. The results revealed that the forest fire affected site along with grazing was with lowest soil moisture; organic carbon and nitrogen content and significantly varied with other sites for most of the soil characteristics. The community forestry and protected sanctuary provide a certain good quality of grasses and subsistence, covering emergency needs and many forest byproducts. Moreover it augment ecological functions; carries valuable indigenous tree species, retains soil moisture and provides continuous supply of organic matter and nutrients